Association of Adiponectin and Vitamin D With Tumor Infiltrating Lymphocytes and Survival in Stage III Colon Cancer. Issue 5 (23rd July 2021) - Sinicrope, Frank A; Shi, Qian; Smyrk, Thomas C; Goldberg, Richard M; Cohen, Steven J; Gill, Sharlene; Kahlenberg, Morton S; Nair, Suresh; Shield, Anthony F; Jahagirdar, Balkrishna N; Jacobson, Sawyer B; Foster, Nathan R; et al.
Abstract: Background: Adipocyte-derived adiponectin may play a role in the host inflammatory response to cancer. We examined the association of plasma adiponectin with the density of tumor-infiltrating lymphocytes (TILs) in colon cancers and with vitamin D, clinicopathological features, and patient survival. Methods: Plasma adiponectin and 25-hydroxyvitamin D [25(OH)D] were analyzed by radioimmunoassay in 600 patients with stage III colon cancer who received FOLFOX-based adjuvant chemotherapy (NCCTG N0147 [Alliance]). TIL densities were determined in histopathological sections. Associations with disease-free survival (DFS), time to recurrence, and overall survival were evaluated by multivariable Cox regression adjusting for potential confounders (ie, body mass index, race, TILs, and N stage). All statistical tests were 2-sided. Results: We found a statistically significant reduction in adiponectin, but not 25(OH)D, levels in tumors with high vs low TIL densities (median   =   6845 vs 8984 ng/mL; P = .04). A statistically significant reduction in adiponectin was also observed in obese (body mass index >30 kg/m 2 ) vs nonobese patients (median   =   6608 vs 12 351 ng/mL; P  < .001), in men vs women (median   =   8185 vs 11 567 ng/mL; P  < .001), in Blacks vs Whites or Asians (median   =   6412 vs 8847 vs 7858 ng/mL; P  < .03), and in those with fewer lymph node metastases (N1 vs N2: median   =   7768 vs 9253 ng/mL; P  = .01). Insufficiency of 25(OH)D (<30 ng/mL) was detected in 291 (48.5%) patients. In multivariable analyses, neither adiponectin nor 25(OH)D were associated with a statistically significant difference in DFS, overall survival, or time to recurrence in models adjusted for potential confounders. We found a statistically significant association of TILs with prognosis, yet no such interaction was observed for the association of adiponectin with TILs for DFS. Conclusions: Lower circulating adiponectin levels were associated with a statistically significant increase in TIL densities in colon cancers, indicating an enhanced antitumor immune response. In contrast to TILs, neither adiponectin nor 25(OH)D was independently prognostic.